Effect of temporary cessation of milking and estradiol combination on the antimicrobial components in goat milk. (20th December 2022) - Purba, Fika Yuliza; Ishimoto, Yoshihisa; Nii, Takahiro; Suzuki, Naoki; Isobe, Naoki
Abstract: A temporary cessation of milking is widely used in Japan to treat mastitis in dairy cows. Exogenous administration of estradiol (E2) is known to inhibit milk production in dairy cows. Therefore, we aimed to evaluate the effects of the temporary cessation of milking in combination with E2 administration on the antimicrobial components of goat milk. Twelve goats, divided into two groups—with and without E2 injection (E2 and control group, respectively), were subjected to cessation of milking in both udder halves for 3 d (day 0–2). Milk yield in the E2 group was significantly lower than that in the control group on days 7 to 10. The concentrations of cathelicidin-2, IgA, and lactoferrin in the E2 group were significantly higher than those in the control group. These results suggest that the temporary cessation of milking with simultaneous E2 administration leads to a higher concentration of certain antimicrobial components in milk than that observed after using cessation of milking alone. Thus, this combination may contribute to a stronger innate immune system and a faster recovery from mastitis, and might prove to be an alternative to antibiotic treatment upon further research. Highlights: 3-d milking cessation with estradiol (E2) injection enhances mammary gland immunity. Milk yield decreases in E2-injected goats 4–5 d after resuming milking. SCC increases in E2-injected goats 4–5 d after resuming milking. Antimicrobial component levels in E2-injected goats are higher than in controls. This combination therapy for mastitis may be an alternative to antibiotic treatment.